Peran Edupreneurship Berbasis Teknologi Digital pada UMKM Terhadap Keberlanjutan Usaha - Pramudita, Rifkiansyah Aryasatya; muhtarom, Ahmad shofi; Sandi A, Aprianto; Nurharyanto, Riyan Tri; Abduh, Haziki; Nugroho, Adi Septian; Rahmawati, Imelda Dian (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Industry 4.0 era has created a significant transformation in the business environment, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This research explores the opportunities, challenges, and the role of digital-based edupreneurship in supporting MSME development in the digital era. Through literature review and analysis of various empirical studies, this paper identifies that digital technology adoption provides strategic advantages for MSMEs, including market reach expansion, operational efficiency improvement, and marketing strategy optimization. However, challenges such as digital divide, technological literacy limitations, and initial investment costs remain primary barriers. Digital-based edupreneurship is proposed as a comprehensive solution to address these challenges, focusing on enhancing digital skills, e-commerce platform access, and MSME innovation capacity development. The research concludes that collaboration between universities, government, and business actors is crucial for driving sustainable digital transformation of MSMEs. By examining the intersection of education, entrepreneurship, and digital technology, this study provides insights into strategic approaches for MSME growth and competitiveness in an increasingly digital global marketplace.